Evaluating Gifted Students’ Enrichment Curricula in Kuwait according to International Standards from the Students and Teachers’ Perspective - Al-Sharika, Falah hammoud Hussein (Journal of Curriculum and Teaching Methodology, 2022)
The study sought to show the differences in the evaluation of enrichment curricula dedicated for gifted students in Kuwait according to the international standards according to the students and teachers’ perspectives. The social survey method was used, and the scale for evaluating the enrichment curricula for gifted students was distributed to a sample of (175) male and female students. Academic (2021-2022). Advanced evaluation scales were adopted to evaluate the gifted programs according to the international standards. The study also showed that there is an average degree of gifted students’ enrichment curricula’s evaluation according to international standards from the student’s general perspective. The study confirmed a statistically significant differences in the gifted students’ enrichment programs’ evaluation in Kuwait according to international standards for the gifted students’ programs according to international standards from the students and teachers’ perspectives, in favour of the teachers. The study indicated that there are apparent in the gifted students’ enrichment curricula evaluation level according to the international standards prom the students’ perspective according the number of years in which students are present in the schools, in favour of those who are present for one year. The study recommends that the curriculum include the positions and activities that stimulate what the gifted posses of mental and creative capacities and identifying it; selecting scientifically and professionally qualified gifted teachers according to their ability to build and implement gifted programs in addition to providing them with continuous professional development.